PSYCHOLOGICAL ASPECTS OF TEACHER’S PROFESSIONAL TRAINING - Svetlana A. Yelantseva (Высшее образование в России)
The article dwells upon the psychological aspects of teachers’ professional training. The system aimed at formation of teacher’s psychological competency was worked out at Ershov Ishim Teachers Training Institute. Teacher’s psychological competency includes such components as knowledge of psychological patterns and age-related peculiarities, skills in applying psychological knowledge in pedagogical activities, and personal traits necessary for organization of effective professional communication. These components are formed by stages within the proposed system.